2010
DOI: 10.1038/ajg.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gastrointestinal Symptoms According to Gender in Rome II Positive IBS and Dyspepsia in a Latin American Population

Abstract: In Mexico, gender differences in FGIDs exist, with both IBS and dyspepsia being more common in women than men. In IBS, symptoms related to constipation and bloating were more common in women, but the dyspepsia group was too small to draw any conclusions. Finally, this is the first study to report that belching is more common in men than women controls not fulfilling criteria for any FGID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
3
29
3
1
Order By: Relevance
“…Different studies from the same country yielded, in some cases, a broad range of results. For example, in the five studies included in this paper from Mexico, the prevalence rates were 4.4%,86 16.0%,84 16.9%,81 28.9%85 and 35.5% 97…”
Section: Resultsmentioning
confidence: 96%
“…Different studies from the same country yielded, in some cases, a broad range of results. For example, in the five studies included in this paper from Mexico, the prevalence rates were 4.4%,86 16.0%,84 16.9%,81 28.9%85 and 35.5% 97…”
Section: Resultsmentioning
confidence: 96%
“…Australian data with a sample size 188 reported that 65% of patients fulfilled IBS criteria and 62% accounted for FD [12]. A Mexican database based on the Rome II Modular Questionnaire showed that IBS accounted for 28.9% of patients whilst FD accounted for only 4.0% [13]. Even in East Asia, data from 4,638 Chinese college and university students revealed a similar prevalence between FD (9.25%) and IBS (8.34%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Possible moderation of the order of incidence by factors known to be associated with FGIDs and available in the database included gender [21][22][23] and socioeconomic disadvantage 24 (Townsend score 25 ) and some socioeconomic background.…”
Section: Study 1: General Practice Medical Record Reviewmentioning
confidence: 99%
“…Factors known to be associated with FGIDs and available in the database were gender [21][22][23] and socioeconomic disadvantage 24 (Townsend score 25 ). The percentage of residents in the patient's locality that were white and, separately, black were included as proxies for other social phenomena.…”
Section: Moderation Of Order Of Incidencementioning
confidence: 99%